Intramolecular Radical Carboaminoxylation of Aryl Amines - Hartmann, Marcel; Gerleve, Carolin; Studer, Armido (Synlett, 2016)
Cyclizing radical carboaminoxylation of various aryl amines is presented. The aryl diazonium salts in situ generated from the corresponding aryl amines are reduced by tetra-n-butylammonium iodide (TBAI) to give the corresponding aryl radicals. These aryl radicals undergo 5-exo and 6-exo cyclization. Subsequent trapping with TEMPO or various other nitroxides provides the corresponding cyclized carboaminoxylated products in moderate to very good yields.
Keywords: carboaminoxylation; in situ diazotation; aryl radicals; radical cyclization; nitroxides